Digital Media and Textuality : From Creation to Archiving - Maduro, Daniela Côrtes (Medienumbrüche ;, 2018)
Due to computers' ability to combine different semiotic modes, texts are no longer exclusively comprised of static images and mute words. How have digital media changed the way we write and read? What methods of textual and data analysis have emerged? How do we rescue digital artifacts from obsolescence? And how can digital media be used or taught inside classrooms? These and other questions are addressed in this volume that assembles contributions by artists, writers, scholars and editors such as Dene Grigar, Sandy Baldwin, Carlos Reis and Frieder Nake. They offer a multiperspectival view on the way digital media have changed our notion of textuality.